A comparative study of supraglottic airway devices Baska mask and ProSeal-laryngeal mask airway in short gynaecological procedures - Kachakayala, Ranjith Kumar; Bhatia, Parmeet; Singh, Shalendra; Dwivedi, Deepak (International Journal of Research in Medical Sciences, 2019)
Background: Baska Mask® (BM) a newer Supraglottic Airway Device (SAD) considered to cause low incidence of Postoperative Pharyngolaryngeal Complications (POPC). This study was designed to assess efficacy, safety and early and late POPC between BM and commonly use ProSeal LMA (PMLA). Methods: Patients between 18 to 60 years of age undergoing elective short gynecological procedures were randomized into two groups, to receive ventilation with either BM (group 1, n=50) or an PMLA (group 2, n=50). Results: There was no significant difference in the ease of insertion for both the devices (p<0.24). There was no significant difference in the number of attempts for both the devices (p<0.69). When compared to PLMA, the time (in seconds) required for insertion of BM was significantly less in duration (20.9 vs. 16) (p<0.0001). Between the two groups significant hemodynamic changes noticed after removal of SGA. The blood staining of device was similar in both groups. Failure to place device, postoperative complication like laryngospasm and bronchospasm did not occur in both BM and PLMA groups. Conclusions: In conclusion, findings of this study support that BM takes significantly shorter placement time and provides a better seal as compared to PLMA but without any reduction in laryngopharyngeal complications.